Meeting the challenges of the EU-2020 agenda: A future-oriented indicator analysis for the EU-countries - Horst Hanusch; Yasushi Hara (Universität Augsburg, Institut für Volkswirtschaftslehre, 2016)
Future-orientation or innovativeness is a leading credo in the EU's economic policy agenda of the 21st century. It started in the year 2000 with the Lisbon Agenda, the first 10 years plan in which Europe should have become the most competitive and dynamic knowledge-based economic region in the world. And, it continued in 2010 with the second 10 years framework program "EU 2020" which again is concentrating on research and innovations in the technological, but also in the social (political) and ecological field. The evolving quantitative and qualitative effects summarize under the strategy of "smart, inclusive and sustainable growth" (European Union, 2010). The aim of our study is to deal with these grand European visions and to focus on the "emerging future" of the EU countries. How do the EU member states handle their economic future? Does there exist a certain pattern of future-orientation? Can specific similarities or dissimilarities between the single countries be observed and satisfactorily explained? To give an answer to these questions we use an empirical indicator approach combined with cluster analysis. This approach, however, has to be based on a specific model of future-orientation or economic development. Such a model determines the theoretical scaffold of the study and provides the necessary ingredients for an empirical application. In our study we will use "Comprehensive Neo-Schumpeterian Economics" (CNSE) as an analytical framework (Hanusch and Pyka, 2007a). This approach is based (a) on the principle of innovation as the main driving force and the engine of development coupled (b) with the notion of future-orientation penetrating all spheres of socio-economic life in developed as well as in developing countries.
urn:nbn:de:bvb:384-opus4-710810
Keywords: B52; C8; O57; 330; Schumpeterian economics; development; country studies; data estimation